2020
DOI: 10.1002/ccd.28940
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of post‐stent optical coherence tomography findings: Layered versus non‐layered culprit lesions

Abstract: Objectives This study aimed to investigate the vascular response of lesions with a layered phenotype. Background Recent studies have shown that layered plaques at culprit lesions detected by optical coherence tomography (OCT) have greater plaque burden and more inflammatory features than non‐layered plaques. Methods This is a retrospective observational study. A total of 193 target lesions from 193 patients [100 patients with acute coronary syndromes (ACS) and 93 with stable angina pectoris (SAP)] who had unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…In the clinical therapeutic interventions, Kurihara et al found that stents had limited dilation and more eccentric lumens in non-healed plaques after PCI in patients with ACS compared with healed plaques. Afterward, they found that the presence of healed plaques in culprit vessels was an independent predictor of revascularization rate during a 2-year follow-up ( 26 , 27 ). In the early days, the complex characteristics of TCFA and microvessels as determined by OCT seemed to be potential predictors of subsequent progression of coronary plaque in patients with CAD ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical therapeutic interventions, Kurihara et al found that stents had limited dilation and more eccentric lumens in non-healed plaques after PCI in patients with ACS compared with healed plaques. Afterward, they found that the presence of healed plaques in culprit vessels was an independent predictor of revascularization rate during a 2-year follow-up ( 26 , 27 ). In the early days, the complex characteristics of TCFA and microvessels as determined by OCT seemed to be potential predictors of subsequent progression of coronary plaque in patients with CAD ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is subjective and involves the risk of inter-observer variability. Indeed, inter-observer kappa values were not excellent (0.73–0.78) in previous studies 10 , 28 , 30 , 31 . Therefore, we devised the DL algorithm for the objective diagnosis of layered plaque.…”
Section: Discussionmentioning
confidence: 71%
“…In this study, we also observed the impact of other types of B2/C lesions, such as eccentric and calcified lesions, on the HP. One study concluded that lesions with HP had more eccentric lumens after stent implantation 26 . Another study found that calcium deposition was associated with plaque stability 27 .…”
Section: Discussionmentioning
confidence: 99%
“…One study concluded that lesions with HP had more eccentric lumens after stent implantation. 26 Another study found that calcium deposition was associated with plaque stability. 27 Our study showed that eccentric and calcified lesions were more common in patients with HP than without HP among the total study population.…”
Section: Discussionmentioning
confidence: 99%